Design and Simulation Analysis of a New Type of Planetary Gear Plug-in Hybrid Power System - Li Zhiming; Wang Yulin; Tang Jinqin; Hao Xiyang (Jixie chuandong)
A new type of hybrid transmission device for plug-in hybrid electric vehicle（ PHEV） is present with planet gearbox. The parameters of the planet gearbox are obtained by using optimization method. In order to assess the economic efficiency and dynamic performance,the simulation model of the PHEV is set up based on the ADVISOR software,the vehicle parameters of a domestic SUV are used. The PHEV are simulated in NEDC cycle for charge depleting mode and charge sustaining mode,the results show that the presented new PHEV system can satisfy the requirement of new standard GB/T 32694—2016. The new system use only one motor and the hybrid device are compact,so that it expend low price and take small space in application.